Cognitive and Behavioral Outcomes of Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Of approximately 14,000 children enrolled in a British Child Health and Education Study, 398 identified with febrile convulsions (FC) were assessed at age 10 years at Addenbrooke's Hospital, Cambridge, and the University of Bristol, UK.